Multi-criteria assessment to screen climate smart rice establishment techniques in coastal rice production system of India - Mohapatra, Kiran Kumar; Nayak, A. K.; Patra, R. K.; Tripathi, Rahul; Swain, Chinmaya Kumar; Moharana, K. C.; Kumar, Anjani; Shahid, Mohammad; Mohanty, Sangita; Garnaik, Saheed; Nayak, Hari Sankar; Mohapatra, Simran; et al. (Frontiers in Plant Science, 2023)
Introduction Conventional rice production techniques are less economical and more vulnerable to sustainable utilization of farm resources as well as significantly contributed GHGs to atmosphere. Methods In order to assess the best rice production system for coastal areas, six rice production techniques were evaluated, including SRI-AWD (system of rice intensification with alternate wetting and drying (AWD)), DSR-CF (direct seeded rice with continuous flooding (CF)), DSR-AWD (direct seeded rice with AWD), TPR-CF (transplanted rice with CF), TPR-AWD (transplanted rice with AWD), and FPR-CF (farmer practice with CF). The performance of these technologies was assessed using indicators such as rice productivity, energy balance, GWP (global warming potential), soil health indicators, and profitability. Finally, using these indicators, a climate smartness index (CSI) was calculated. Results and discussion Rice grown with SRI-AWD method had 54.8 % higher CSI over FPR-CF, and also give 24.5 to 28.3% higher CSI for DSR and TPR as well. There evaluations based on the climate smartness index can provide cleaner and more sustainable rice production and can be used as guiding principle for policy makers.